2014
DOI: 10.4236/jbise.2014.712094
|View full text |Cite
|
Sign up to set email alerts
|

Bone and Soft Tissue Blood Flow during Normobaric and Hyperbaric Oxygen Breathing in Healthy Divers

Abstract: Purpose: The study aimed to investigate, using a photoplethysmographic (PPG) technique, how pulsatile blood flow within the patellar bone and skin over the patella reacts to normobaric (NBO) and hyperbaric oxygen breathing (HBO). Methods: Eleven healthy volunteers, breathed air or oxygen. Subjects were blinded to breathing gas. A range of partial pressures of oxygen were administered in 10 minute intervals: 21 kPa, 101 kPa (NBO), 21 kPa, (compression to 280 kPa), 59 kPa, 280 kPa (HBO), 59 kPa, (decompression),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Twenty‐one studies were identified using near infrared spectroscopy (NIRS) and 10 studies were identified using photoplethysmography (PPG) non‐invasively on in vivo bone tissue . Fifty‐seven studies were identified using laser Doppler flowmetry (LDF) in vivo of which 56 were intra‐operative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐one studies were identified using near infrared spectroscopy (NIRS) and 10 studies were identified using photoplethysmography (PPG) non‐invasively on in vivo bone tissue . Fifty‐seven studies were identified using laser Doppler flowmetry (LDF) in vivo of which 56 were intra‐operative.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 10 PPG studies from two research groups investigating the patella and tibia . These studies utilized bespoke PPG systems making use of an isobestic 804 nm NIR wavelength to measure the amplitude of pulsatile flow in bone tissue based on attenuation changes in reflected signal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations